2022
DOI: 10.3168/jds.2021-21159
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with N-carbamoylglutamate during the transition period improves the function of neutrophils and reduces inflammation and oxidative stress in dairy cows

Abstract: The aim of this study was to investigate the effects of N-carbamoylglutamate (NCG) supplementation during the transition period on the functions of blood polymorphonuclear neutrophils (PMN), inflammation, and oxidative stress in dairy cows. Thirty multiparous Chinese Holstein dairy cows at wk 4 before parturition were blocked into 2 groups by parity, body weight, and milk yield of previous lactation, and randomly allocated to 2 dietary treatments of basal diet supplemented without (control, n = 15) or with 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Targeted interventions with antioxidants during the entire gestation has proved to counteract oxidative stress in naturally undernourished pregnant ewes, improving fetal growth, regardless of the liter size [ 25 ]. The NCG antioxidant capacity has been demonstrated in lambs [ 38 , 39 ] and dairy cows [ 40 ] and has also been proposed to improve the maternal–fetal–placental antioxidant capability in underfed twin-bearing ewes (50% NRC) at 110 dga by increasing TAC and reducing MDA in maternal and fetal plasma, and in the caruncle and cotyledon, when supplemented from day 35 to 110 of gestation [ 18 ] via modification of specific metabolic pathways [ 15 ]. However, in the present study, maternal supplementation with NCG during late gestation resulted in no effects on the materno-fetal antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted interventions with antioxidants during the entire gestation has proved to counteract oxidative stress in naturally undernourished pregnant ewes, improving fetal growth, regardless of the liter size [ 25 ]. The NCG antioxidant capacity has been demonstrated in lambs [ 38 , 39 ] and dairy cows [ 40 ] and has also been proposed to improve the maternal–fetal–placental antioxidant capability in underfed twin-bearing ewes (50% NRC) at 110 dga by increasing TAC and reducing MDA in maternal and fetal plasma, and in the caruncle and cotyledon, when supplemented from day 35 to 110 of gestation [ 18 ] via modification of specific metabolic pathways [ 15 ]. However, in the present study, maternal supplementation with NCG during late gestation resulted in no effects on the materno-fetal antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress level was significantly increased in the mammary gland of dairy cows. In addition to the typical reductions in milk production, persistent oxidative stress affects lactation quality and reduces performance in dairy cows [7,36]. An increasing number of studies have shown that natural Chinese herbal extracts elicit protective effects against oxidative stress and inflammation, such as paeonol [37], Curcuminoids [38], and Houttuynia cordata Thunb [39].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 By stimulating lymphocyte proliferation and modulating cytokine synthesis, NCG supplementation can improve the growth performance, intestinal integrity, antioxidant status, and intestinal mucosal immunity of some animals. [29][30][31] Furthermore, dietary NCG benefits the growth of the gut microbiota and modulates rats' metabolic processes, such as amino acid and lipid metabolisms. [32][33][34] Previous studies showed that dietary chitosan oligosaccharides could modulate immunity in piglets by regulating the microflora and Th17/Treg cells after an enterotoxigenic Escherichia coli challenge.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐Carbamylglutamate (NCG) a structural analog of N ‐acetylglutamate, can stimulate endogenous Arg synthesis by activating the urea cycle and Arg synthesis pathway's rate‐limiting carbamoyl‐phosphate synthase 27,28 . By stimulating lymphocyte proliferation and modulating cytokine synthesis, NCG supplementation can improve the growth performance, intestinal integrity, antioxidant status, and intestinal mucosal immunity of some animals 29‐31 . Furthermore, dietary NCG benefits the growth of the gut microbiota and modulates rats’ metabolic processes, such as amino acid and lipid metabolisms 32‐34 .…”
Section: Introductionmentioning
confidence: 99%